Integration of flexible corporate demographic policy tools into the personnel management system - Natalya V. Tonkikh; Marina V. Chudinovskikh; Svetlana V. Begicheva (Управленец)
Amid staff shortages and rising labour costs, many Russian enterprises are looking for non-material methods to man age personnel. Organizational, labour and socio-psychological aspects of employee incentives are closely linked to the corporate demographic policy tools. The article aims to analyse the demand for flexible working arrangements for employees with family responsibilities, as well as to determine the opportunities for integrating flexible organizational and labour tools of corporate de mographic policy into the personnel management system. Flexibilization theory in the context of corporate demographic policy constitutes the methodological basis of the study. The standard methods of structured personal interviews, frequency analysis with equality of proportions hypothesis test using a chi-square statistic, and comparison of mean values based on the Kruskal Wallis test were applied. The empirical evidence includes collective agreements and local regulations of the largest employers in the Russian Federation, as well as results of a sociological survey conducted in June–September, 2023 (the analyzed sample cov ered 2,804 respondents). The study statistically proves that employees working flexible hours are more satisfied with their job and life compared to those with rigid schedules. It also shows that flexible working arrangements are in demand among employees with parental commitments. The paper presents a model and an algorithm for integrating flexible organizational and labour tools of corporate demographic policy into the personnel management system. We develop a list of HR metrics and identify potential positive implications of this integration through strengthening the HR brand, increasing employee loyalty and engagement, and reducing staff turnover.